Association between social support and leisure-time physical activity among high school students - Luiza Isnardi Cardoso Ricardo; Airton Rombaldi; Jorje Otte; Ana Perez; Mario Azevedo (Revista Brasileira de Atividade Física e Saúde)
The aim of this study was to analyze the association between social support and leisure-time physical activity level in students from the federal network of Rio Grande do Sul, and their relationships with sex and the different types and sources of social support. A cross-sectional study was carried out in order to make up a sample of 833 students aged between 13 and 25 years, enrolled from the 1st to the 3rd year in a technical high school from four campuses of the Federal Institute of Education, Science and Technology of Rio Grande do Sul (IFsul). Among the respondents, 50.3% (CI95% 46.9 - 53.7) of the sample was considered physically active during leisure-time, and boys (64.7%; CI95% 59.9 – 69.1) were more active than girls (36.8%; CI95% 31.7 – 40.9). In the adjusted analysis, individuals who had higher social support from parents showed a higher probability of being active in comparison to those with less social support, showing the Prevalence ratio (PR) of 2.55 (CI95% 1.67-3.90) among girls and 1.64 (CI95% 1.20-2.23) among boys. About the social support from friends, boys located in the more elevated level of social support had greater probability of being active related to those with lower social support. (RP 2.19; CI95% 1.46-3.26). The same analysis among girls has also shown significant results (PR 1.67; CI95% 1.08-2.58). It was concluded that social support from parents and friends is an important tool in order to promote physical activity in adolescents.